Angiosarcoma of the Left Atrium: A Case Report - Schlachtenberger, Georg; Gerfer, Stephen; Kröner, Axel; Wahlers, Thorsten (The Thoracic and Cardiovascular Surgeon Reports, 2018)
Background Primary cardiac tumors are rare, and many diagnosed tumors are benign with an incidence of 0.001% to 0.03%. The primary angiosarcoma is one of the malignant entities.Discussion We discuss a case report of a 76-year-old male who underwent a preoperative diagnosis for an upcoming shoulder operation when his cardiologist diagnosed a large cardiac tumor. The patient was referred to our department where he received further diagnostics. The transesophageal echocardiography and the cardiac-magnetic resonance imaging showed a massive tumor with a dimension of 8.6 × 5.6 cm with no signs of malignity.Method The operation was performed by standard median sternotomy. The tumor was adherent to the septum and the left atrium, and we were able to remove the specimen in toto. Pathological examinations showed an angiosarcoma with neovascularization and core expression of ERG+ and cytoplasmic expression of CD31+/CD34+, due to the size of the mass. The resection of primary cardiac tumors is mostly the therapy of choice, but in this case concerning an angiosarcoma the prognosis is poor, considering that the angiosarcoma responds very badly to chemotherapy and radiotherapy.
Keywords: sarcoma; myxoma